Comprehensive Midwifery Care For Mrs. “Y” G3P2A0 Through The Use Of Perineal Massage Video To Prevent Perineal Laceration At Melong Asih Community Health Center - Nabilah, Naifah; Putriastuti, Widya; Fatonah, Sofa; Maryati, Sri (Riviera Publishing, 2025)
Vaginal delivery is often accompanied by anatomical changes in the perineum, one of which is perineal laceration, experienced by approximately 85% of women who give birth spontaneously. This laceration can affect the mother's recovery and quality of life during the postpartum period. Perineal massage can help prevent tears by increasing the elasticity of perineal tissue, preparing it for stretching during childbirth, and reducing the risk of tears. This study aims to provide comprehensive care using perineal massage techniques from pregnancy to prevent perineal lacerations. The method used is descriptive with a case study approach, data collection through interviews and physical examinations. The study subject was Mrs.